Growth performance and cecal microbiota of broiler chicks as affected by drinking water disinfection and/or herbal extract blend supplementation - Wei Shuang Meng; Qiangqiang Zou; Yingying Xiao; Wei Ma; Jiawen Zhang; Tieliang Wang; Desheng Li (Poultry Science, 2023)
ABSTRACT: Environmental exposures during early life are important for animals’ intestinal microbiota composition and their production performance. This experiment investigated the growth performance, hematology parameters, jejunal morphology, and cecal microbiota of broiler chicks as affected by exogenous factors from the aspects of drinking water quality and dietary manipulation. A total of 480-day-old broiler chicks (Arbor acre; 41.59 ± 0.88 g) were randomly assigned into 4 groups (CON, HWGM, CA, CAHWGM). Each group had 6 replicates with 20 birds per replicate. Broiler chicks in CON group were fed with basal diet and drank normal drinking water; in HWGM group were fed with basal diet supplemented with 1.5g/kg herbal extract blend (hops, grape seed, and wheat germ) and drank normal drinking water; in CA group were fed with basal diet and drank sodium dichlorocyanurate (50 mg/L) treated-drinking water; in CAHWGM group were fed with basal diet supplemented with 1.5 g/kg herbal extract blend and drank chlorinated drinking water. The experimental period was 42 d. We found that broiler chicks drank chlorinated drinking water led to an increase in body weight gain and feed efficiency during d 22 to 42 and 1 to 42, as well as a decrease in cecal Dysgonomonas and Providencia abundance. Dietary supplementation of herbal extract blend increased cecal Lactobacillus and Enterococcus abundance, whereas decreased Dysgonomonas abundance. Moreover, we observed that cecal Dysgonomonas abundance synergistically decreased by treating drinking water with sodium dichlorocyanurate and supplementing herbal extract blend to the diet. Therefore, results obtained in this study indicated that providing chlorinated drinking water is an effective strategy to improve the growth performance of broiler chicks by regulating intestinal microbiota. Additionally, dietary supplementation of herbal extract blend alone or combined with chlorinated drinking water is able to regulate cecal microbiota.